2018
DOI: 10.1136/vetreco-2017-000237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three types of horseshoes and unshod feet on selected non‐podal forelimb kinematic variables measured by an extremity mounted inertial measurement unit sensor system in sound horses at the trot under conditions of treadmill and soft geotextile surface exercise

Abstract: Therapeutic farriery is part of the management of certain orthopaedic conditions. Non-podal parameters are important as most horses shod with therapeutic shoes are expected to perform again and the choice of shoe type may be influenced by the effects they may have on gait. The aim of this prospective study was to evaluate the effects of three different shoe designs and unshod front feet on forelimb non-podal kinematic variables using an extremity mounted inertial measurement unit (IMU) system under conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…One such study has shown that in unshod horses at a slow trot, the range of vertical displacement of the scapular spine, representing movement of the trunk, is 10% lower than in shod horses (Willemen, Savelberg, & Barne‐veld, 1999). Another study has found that unshod horses at slow trot (~3.3 m/s) show 7.9% less range of motion of the forelimb compared with shod horses, with the effect being more pronounced on a soft geotextile surface (Stutz, Vidondo, Ramseyer, Maninchedda, & Cruz, 2018). The relevance of these findings for high‐speed trotting remains to be investigated, but if the 8%–10% reduction in body vertical displacement persists at high speed, there could be a positive impact on racing performance.…”
Section: Introductionmentioning
confidence: 99%
“…One such study has shown that in unshod horses at a slow trot, the range of vertical displacement of the scapular spine, representing movement of the trunk, is 10% lower than in shod horses (Willemen, Savelberg, & Barne‐veld, 1999). Another study has found that unshod horses at slow trot (~3.3 m/s) show 7.9% less range of motion of the forelimb compared with shod horses, with the effect being more pronounced on a soft geotextile surface (Stutz, Vidondo, Ramseyer, Maninchedda, & Cruz, 2018). The relevance of these findings for high‐speed trotting remains to be investigated, but if the 8%–10% reduction in body vertical displacement persists at high speed, there could be a positive impact on racing performance.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to study initiation, a power analysis and sample size calculation a were performed. Given the mean ± SD GRF data reported in a previous study 1 and assuming a significance level of 5% (α = 0.05) and power of 80% (β = 0.20), it was determined that a minimum of 5 horses would need to be evaluated for the planned analyses.…”
Section: Animalsmentioning
confidence: 99%
“…H orseshoes are frequently modified to enhance traction for horses that travel on paved surfaces for work, pleasure, or entertainment. [1][2][3][4] The types of equids that travel on paved surfaces range from draft horses to ponies, and the use of those animals varies from a basic means of transportation in Amish communities 5 to police service horses 6 and tourist wagon and buggy rides. 3,7 Information is available about the effect of horseshoe modifications such as toe grabs and studs on traction and other gait kinetics for horses used for racing and pulling, but little is known about the kinetic effects of other common horseshoe modifications used to enhance traction, such as calks, tungsten carbide granules, or plastic composites.…”
mentioning
confidence: 99%
“…However, very few controlled scientific studies have been conducted to rigorously ascertain the therapeutic efficacy of such strategy ( 12 ). Multiple shoeing methods have been conceived, such as z-bar shoes (open area of shoe is intended to reduce weight bearing on the palmar area of the hoof, reducing trauma and promoting healing) ( 13 ), egg bar shoes (increase the weight-bearing surface and create a larger area of posterior support for the foot and leg) ( 14 ), toe wedges and heel wedges (used on the rear palmar aspect of a collapsed heel region of a hoof wall) ( 8 ). These interventions are postulated to promote distal limb health, through supporting the joints of the lower limb and reducing unwanted biomechanical forces applied by the farrier if adverse conformational traits are identified.…”
Section: Prophylactic Shoeingmentioning
confidence: 99%